FREQUENCY OF VARIOUS TYPES OF LEUKAEMIAS DIAGNOSED AT PAF HOSPITAL MIANWALI: Types of Leukaemias Diagnosed - Ahmad, Saqib Qayyum; Yusuf, Rizwan; Burney, Shamaila (Pakistan Armed Forces Medical Journal, 2015)
Objective: To determine the frequencies of various types of leukaemias in a secondary care hospital.Original Article Study Design: DescriptivePlace and Duration of Study: PAF Hospital Mianwali, from  Jan 2009 to Dec 2012.Material and Methods: Record of all the cases of acute lymphoblastic leukaemia (ALL), acute myeloid leukaemia (AML), chronic lymphocytic leukaemia (CLL) and chronic myeloid leukaemia (CML) diagnosed during the period of study was retrieved from the laboratory and total number of leukaemia cases were counted. The ages and the genders of the patients were noted. Median age at diagnosis for each type of leukaemia was worked out. Frequency of each leukaemia type was noted and relative frequency was calculated as percentage.Results: Out of a total of 67 patients, AML was diagnosed in 22 (32.8%), CML in 16 (23.8%), ALL in 15 (22.4%) and CLL in 14 (20.9%) cases. Median age at diagnosis for ALL, AML, CLL and CML was 5, 41, 70 and 40 years respectively while male to female ratio was 2.7, 1.4, 1.3 and 1.5 respectively.Conclusion: AML was the commonest leukaemia type, followed by CML, ALL and CLL. In children, ALL was found to be four times more common than AML.